PERBANDINGAN MODEL PEMBELAJARAN SAVI DAN PBL TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI PADA SISWA XI SMA NEGERI 9 KOTA JAMBI - Sri Laraswati, Pratiwi Indah Sari (Universitas Batanghari Jambi, 2020)
Abstract This study aims to determine the comparison of the use of learning models applied, namely SAVI learning models and PBL learning models in economic subjects with fiscal and monetary policy material in class XI IPS SMA Negeri 9 Jambi City. Based on research, it can be explained that the learning model can help students better understand the material being taught and be more focused in learning. The learning model used can make students more active and provide convenience in the learning process. Therefore, the role of the teacher is needed in order to understand the use of models, methods, strategies, and approaches in carrying out teaching and learning activities. The results of the study, obtained an average value of -0.53. Thus, it can be concluded that the SAVI learning model can help students be more active and enthusiastic in learning. Thus, it can be explained that the SAVI learning model can provide convenience and make students eager to learn this can be seen from the completeness of student learning. Keyword: SAVI, PBL, Learning Outcomes.